Prior Staphylococcus Aureus Nasal Colonization: A Risk Factor for Surgical Site Infections Following Decolonization. Issue 12 (December 2016) - Ramos, Nicholas; Stachel, Anna; Phillips, Michael; Vigdorchik, Jonathan; Slover, James; Bosco, Joseph A.
Abstract : Introduction: Staphylococcus aureus (S aureus) decolonization regimens are being used to mitigate the risk of surgical site infection (SSI). However, their efficacy is controversial, with mixed results reported in the literature. Methods: Before undergoing primary total knee arthroplasty (TKA), total hip arthroplasty (THA), or spinal fusion, 13, 828 consecutive patients were screened for nasal S aureus and underwent a preoperative decolonization regimen. Infection rates of colonized and noncolonized patients were compared using unadjusted logistic regression. An adjusted regression analysis was performed to determine independent risk factors for SSI. Results: The rate of SSI in colonized patients was 4.35% compared with only 2.39% in noncolonized patients. In our TKA cohort, unadjusted logistic regression identified S aureus colonization to be a significant risk factor for SSI (odds ratio [OR], 2.9; P < 0.001). After controlling for other potential confounders including age, body mass index, tobacco use, and American Society of Anesthesiologists score, an SSI was 3.8 times more likely to develop in patients colonized with S aureus (OR, 3.8; P = 0.0025). The THA and spine colonized patients trended toward higher risk in both unadjusted and adjusted models; however, the results were not statistically significant. Discussion: The results of our study suggest that decolonization may not be fully protective against SSI. The risk of infection after decolonization is not lowered to the baseline of a noncolonized patient. Level of Evidence: Level IV